Sport and Physical Activity in Isolation Caused by Coronavirus - Branko Krivokapic (Journal of Anthropology of Sport and Physical Education)
The coronavirus pandemic, officially declared on March 11, 2020, has temporarily stopped the planet, and paralyzed all sports activities. Millions of athletes around the world, locked in four walls, without the possibility of training and competition, faced a new challenge. This study tries to look at the psychological and sociological impact of quarantine on athletes, as well as the economic consequences that the pandemic will leave on the world of sports. Interviews with a sports psychologist, sports worker and former athlete highlighted various aspects of the crisis. The aim of study is to assess how and to what extent a pandemic will change sport, with the conclusion that it will not change the human nature and strong need to engage in it.